2009
DOI: 10.1007/s00467-008-1075-8
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid inhibits oleic acid-induced mesangial cell activation through both cellular reactive oxygen species and inosine monophosphate dehydrogenase 2 pathways

Abstract: The synthesis of extracellular matrix (ECM) in mesangial cells (MCs) plays important roles in the development and progression of renal diseases, including chronic allograft nephropathy. Mycophenolic acid (MPA), an inhibitor of inosine monophosphate dehydrogenase 2 (IMPDH2), suppresses MC proliferation and ECM synthesis. However, the exact inhibitory mechanism of MPA on MCs has not been clearly elucidated. In this study we compared the inhibitory effects of MPA and IMPDH2 reduction [by using small interfering R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The analysis showed that total ROS was significantly increased in AL compared to healthy controls; in contrast, it was decreased in LN compared to AL. It has been demonstrated that cyclophosphamide can induce [ 36 ], whereas, mycophenolate can inhibit ROS production [ 37 , 38 ] in several cell types. Similarly, MDA a marker of lipid peroxidation was increased in AL compared to healthy controls; on the other hand, it was reduced in LN compared to AL.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that total ROS was significantly increased in AL compared to healthy controls; in contrast, it was decreased in LN compared to AL. It has been demonstrated that cyclophosphamide can induce [ 36 ], whereas, mycophenolate can inhibit ROS production [ 37 , 38 ] in several cell types. Similarly, MDA a marker of lipid peroxidation was increased in AL compared to healthy controls; on the other hand, it was reduced in LN compared to AL.…”
Section: Discussionmentioning
confidence: 99%
“…Oleate has been reported to induce myofibroblast phenotype in mesangial cells through transforming growth factor (TGF)-β1 activation, which suggests that elevated FFAs may induce ECM remodeling and renal fibrosis (13). We have observed previously that oleate-induced ROS upregulate fibronectin (FN) in murine mesangial cells (MMCs) (14). …”
mentioning
confidence: 99%
“…These immunosuppressive properties have led to the clinical use of MMF in several forms for treatment of glomerulonephritis and in organ transplantation [17]. In addition, several studies have shown that MMF or MPA may inhibit the production of reactive oxygen species and activation of the mitogen-activated protein kinases such as extracellular signal-regulated kinase 1/2 and p38 kinase in MCs [18,19], decrease the production of lymphocyte-and macrophage-derived cytokines and growth factors, especially TGF-β 1 [20], inhibit ECM deposition [21], and block the proliferation of fibroblasts, vascular smooth muscle and MCs [21]. Furthermore, clinical trials have shown that the combination of MMF and a reduction in the CsA dose may be effective in preventing the progression of chronic allograft nephropathy [22,23].…”
mentioning
confidence: 99%